Zingiber officinale Roscoe Rhizomes Attenuate Oxaliplatin-Induced Neuropathic Pain in Mice - Ji Hwan Lee; Daeun Min; Donghun Lee; Woojin Kim (Molecules, 2021)
Oxaliplatin is a platinum derivative chemotherapeutic drug widely used against cancers, but even a single treatment can induce a severe allodynia that requires treatment interruption and dose diminution. The rhizome of Zingiber officinale roscoe (Z. officinale, ginger), has been widely used in traditional medicine to treat various diseases causing pain; however, its effect against oxaliplatin-induced neuropathic pain has never been assessed. In mice, a single oxaliplatin (6 mg/kg, i.p.) treatment induced significant cold and mechanical allodynia. Cold and mechanical allodynia were assessed by acetone drop and von Frey filament tests, respectively. Water extracts of Z. officinale (100, 300, and 500 mg/kg, p.o.) significantly attenuated both cold and mechanical allodynia induced by oxaliplatin. Intrathecal pre-treatment with the antagonist 5-HT1A (NAN-190, i.t., 1 μg), but not with the antagonist 5-HT2A (ketanserin, i.t., 1 μg), significantly blocked the analgesic effect of Z. officinale against both cold and mechanical allodynia. However, 5-HT3 antagonist (MDL-72222, i.t., 15 μg) administration only blocked the anti-allodynic effect of Z. officinale against cold allodynia. Real-time PCR analysis demonstrated that Z. officinale significantly increased the mRNA expression of the spinal 5-HT1A receptor that was downregulated after oxaliplatin injection. These results suggest that Z. officinale may be a viable treatment option for oxaliplatin-induced neuropathic pain.